Design and Implementation of Fuzzy Logic Based Intelligent Vacuum Robot System for Auto Navigation at Home - Kartiks, Kartika; Jannah Br Lubis, Miftahul; Asran, Asran; Misriana, Misriana (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
The development of technology in the 4.0 era has led to the creation of various smart devices that can ease household chores, including in the field of cleaning. This rapid innovation brings significant changes such as vacuuming robots. A vacuuming robot is an innovative design to solve cleaning automatically. This research aims to design a vacuuming robot using Takagi-Sugeno fuzzy navigation and holonomic movement mapping. This innovation in the field of automation is designed to improve efficiency and accuracy in the cleaning process. This system integrates several main components: Arduino Mega 2560 as the central controller, DSM501A dust sensor for detecting dust levels with a range of 20-150 μg/m³, and HC-SR04 ultrasonic sensor for obstacle avoidance at a distance of 5 60 cm. The drive system uses an L298N motor driver to control the mecanum wheel with a PWM value of 150-250, enabling precise holonomic motion with a position error of 1.2% to 4.1%. The robot can move at a speed of 0.5 m/s in the no-obstacle condition and adjusts to 0.3 m/s when detecting obstacles, with a system response time of 1.5 seconds. Test results showed consistent performance, with maximum speed reaching 873.2 RPM without load and 714.4 RPM with load at PWM 250, while in holonomic motion testing, the robot demonstrated high accuracy in diagonal motion and 360° rotation with a position standard deviation of only 0.7 - 1.5 cm. The Takagi-Sugeno fuzzy system successfully classified the obstacle distance into three categories (near, medium, far) and regulated the motor speed between 350-1100 RPM according to the environmental conditions, proving that the integration between TakagiSugeno fuzzy algorithm and holonomic design resulted in an efficient and adaptive vacuum robot system, capable of effective navigation and cleaning while maintaining high precision in obstacle avoidance.